The Elder Brother - Gans, Eric Lawrence (2024)
This Chronicle is dedicated to the memory of the martyrs of last October 7 and of the sufferings they endured and continue to endure. A long-time Girardian once called me the group’s "elder brother," clearly thinking of John Paul II’s use of that term to designate the Jews, but primarily of the fact that I...